2016
DOI: 10.1002/jsfa.7657
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and fish thickness on the mass transfer kinetics during the cod (Gadus morhua) desalting process

Abstract: Optimum combinations between the process variables analysed are essential in order to speed up the mass transfer kinetics during cod desalting at an industrial scale. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The water‐holding capacity of cod protein increased from a 59.8 g g −1 sample to a 70.4 g g −1 sample after hydrolyzation by Flavorzyme . Mahmoudreze et al . reported that FPH produced from salmon demonstrated a strong water‐holding capacity – even stronger than egg albumen and soybean protein, which are commonly used as commercial water binders in the food industry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water‐holding capacity of cod protein increased from a 59.8 g g −1 sample to a 70.4 g g −1 sample after hydrolyzation by Flavorzyme . Mahmoudreze et al . reported that FPH produced from salmon demonstrated a strong water‐holding capacity – even stronger than egg albumen and soybean protein, which are commonly used as commercial water binders in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…The water-holding capacity of cod protein increased from a 59.8 g g −1 sample to a 70.4 g g −1 sample after hydrolyzation by Flavorzyme. 33 Mahmoudreze et al 34 reported that FPH produced from salmon demonstrated a strong water-holding capacity -even stronger than egg albumen and soybean protein, which are commonly used as commercial water binders in the food industry. Mahmoudreze et al 35 also reported the same trend as this study, showing that, under the same hydrolyzation conditions, in comparison with raw fish protein, the water-holding capacity increased (from 59.8 g g −1 sample to 70.4 g g −1 sample), while the oil-holding capacity decreased (from 6.0 g g −1 sample to 5.0 g g −1 sample).…”
Section: The Oil-holding Capacity and Water-holding Capacity Of Raw Cmentioning
confidence: 99%
“…Before use, salted fish needs to undergo a desalting process, typically taking place in the consumer's kitchen over 24–48 h. Nowadays, with changes in consumer lifestyles and a growing demand for low‐sodium and ready‐to‐use products, there is an increased need for enhanced desalted products. Several desalting methods have been explored to improve the process, including water renewal and stirring (Lorentzen et al ., 2021), adjusting water‐to‐product ratios (Muñoz‐Guerrero et al ., 2010), varying water temperatures (Oliveira et al ., 2014), modifying fillet thicknesses (Oliveira et al ., 2016) and implementing tumbling and injection technologies to reduce desalting time (Bjørkevoll et al ., 2004). However, existing research exclusively centres on a single species, Gadus morhua , and scientific data on the preservation of cold‐desalted fish remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of desalting procedures has been explored to control and optimize the process. For example, desalting with different ratios between water and product (Muñoz-Guerrero, Gutiérrez, Vidal-Brotons, Barat, Gras, & Alcaina, 2010), different product thickness (Oliveira et al, 2016), desalting at different water temperatures (Oliveira et al, 2014), and desalting using technology to minimize the total desalting time applying tumbling and injection technologies (Bjørkevoll et al, 2004).…”
Section: Introductionmentioning
confidence: 99%